Synergistic action of star-shaped Au/Ag nanoparticles decorated on AgFeO2 for ultrasensitive SERS detection of a chemical warfare agent on real samples. Issue 10 (25th February 2020) - Barveen, Nazar Riswana; Wang, Tzyy-Jiann; Chang, Yu-Hsu
Abstract : A novel SERS substrate with AgFeO2 @Au/Ag NPs is prepared to detect paraoxon ethyl with a low LOD, high enhancement factor and good reproducibility. Abstract : It is a great challenge to design and fabricate a cost-effective surface-enhanced Raman spectroscopy (SERS) substrate with excellent reproducibility and sensitivity for reliable environmental analysis. In this work, we have synthesized silver ferrite (AgFeO2 ) interlinked with star-shaped gold/silver (Au/Ag) bimetallic (BM) nanoparticles (NPs) by a simple physical method for the effective detection of an acetylcholinesterase (AchE) inhibitor, paraoxon ethyl (PE). The successful construction of AgFeO2 @Au/Ag NPs was confirmed by UV-Vis spectroscopy, X-ray diffraction, field emission scanning electron microscopy, energy dispersive X-ray spectroscopy and Raman spectroscopy. The enhancement of the SERS signal is achieved by the synergistic effect of the charge transfer mechanism and electromagnetic mechanism. The Raman peak centered at 1357 cm −1 was selected as an ideal peak for the quantitative analysis of PE. The AgFeO2 @Au/Ag NPs can detect PE down to 1 × 10 −8 M with a high analytical enhancement factor of 3.53 × 10 6 and excellent uniformity, as determined randomly from 14 spots (relative standard deviation, RSD, <15%). The recovery values of PE in tap water and tomato juice were from 93.16% to 99.16%. All these results suggest that our proposed SERS substrate has promising potential for the detection of PE. The proposed simple strategy for PE detection by SERS using AgFeO2 @Au/Ag NPs paves the way for future reliable environmental analysis and real sample monitoring.